Comunidade infestante e área de reforma de cana crua submetida a diferentes manejos - Soares, M. B.B.; Bianco, S. [UNESP]; Finoto, E. L.; Bolonhezi, D.; Albuquerque, J. A.A.; Silva, A. A. (FapUNIFESP (SciELO), 2016)
The objective of this study was to evaluate the weed community in a raw sugarcane renovation area with three soil managements and peanut sowing in succession. The experiment was conducted during the 2007/08 season on a raw sugarcane area harvested without prior burning in the last five cuts. A randomized block design with treatments arranged in a split plot and arranged in four replications was used. The main treatments consisted of three cropping systems: conventional tillage, minimum tillage and direct planting, and subplots consisted in the absence (resting) or presence of crop rotation with peanuts. After 135 days from planting peanuts and 180 days of sugarcane harvest, the number of weeds m-2 was counted and the shoot dry biomass of the weeds collected was determined. The data were interpreted by analysis of variance and the means were compared by Tukey’s test at 5% probability so that phytosociological indices a, b, c e d were calculated. The use of soil conservation tillage and peanut in rotation with sugarcane in the renovation areas is effective in controlling weeds and suppression of weed species difficult to control like Cyperus rotundus, Commelina bengalensis, Urochloaplantaginea, and Digitaria nuda.
Weed community in a raw sugarcane renovation area submitted to different soil managements
Keywords: Arachis hypogaea; Direct planting; Fallow; Minimum tillage; Phytosociology; Saccharum spp